Macroeconomic Determinants of Financial Distress in Turkey: An Econometric Analysis - Arslan Ece; Güven Sayılgan (Australasian Accounting, Business and Finance Journal, 2020)
Purpose The purpose of this paper is to investigate the possible links between macroeconomic factors and financial distress in Turkey. Design/methodology/approach Based on the 2009/1-2016/2 quarterly data of macroeconomic factors and the number of filings for bankruptcy postponement, econometric models are developed using forward stepwise regression and classical regression methods to determine the factors influencing financial distress. A vector error correction model is also developed using macroeconomic factors found significant in both methods to investigate the interactions of financial distress with them. Findings In the stepwise regression implementation, performed with 16 independent variables, statistically significant variables entered into the model are industrial production index with negative sign as expected and the unemployment rate with negative sign against the expectations. In the classical regression implementation, performed with 7 independent variables, statistically significant variables are ex ante real interest rate with positive sign and gross domestic product with negative sign as expected and money supply with negative sign against the expectations. The impulse response graphics of a vector error correction model involving bankruptcy postponement, industrial production index and nominal interest rate indicates that bankruptcy postponement is influenced by the shocks both in itself and in industrial production index. Originality/value This is the first study in Turkey investigates macroeconomic determinants of financial distress.
Keywords: Bankruptcy Postponement; Financial Distress; Business Failure; Macroeconomic Determinants